Do We Perceive a Gender Gap in Careers Associated with Technologies? - Morales-Brito, Jenny; Rojas-Cabezas, Germán (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This study aims to establish the perception of the gender gap associated with careers in the technology area. For the above, an online perception survey was designed and applied. Responses were received for a period of 2 weeks. The instrument was applied to students and workers of computer studies as an area related to information and communication technologies. We obtained a sample of 104 people, composed primarily of young men. The data analysis was carried out through descriptive, inferential statistics, exploratory factor analysis, and reliability. In various sections of the study, differences in perception were found between men and women. We established different factors that evidence a perceived gender gap. The underlying dimensions of the gap perception identified were: perception of male superiority, educational competence, and labor competence. In addition, we established the perceived explanatory factors of the gap, which are: educational labor context, social and personal context, and competences and skills in the technological area. We showed that women do consider there is male chauvinism in careers associated with technologies and that the perception of workers is that the career is more appropriate for the male gender. Also, from a gender perspective, the gap is explained, considering the bias of employers as relevant. For future research, we expect to enlarge the sample and contrast the results with those provided by the national socioeconomic characterization survey.